Diseño universal de aprendizaje en la enseñanza de la física: una propuesta de aplicación - Barrón-Hernández, Ana-Rosa; Ramírez-Díaz, Mario-Humberto (Revista Científica, 2023)
During the COVID-19 pandemic, it was difficult to adjust pedagogic practices to digital contexts, where the use of new information and communication technologies (NICTs) in class became necessary. During this time, it was possible to prove that online classes were not only feasible, but also adequate in contexts in which the bulk of the population is nowadays immersed, such as social networks or digital platforms. The use of the Universal Learning Design (UDL) framework in physics constituted an adequate strategy to plan teaching, providing alternatives for students with Attention Deficit Hyperactivity Disorder (ADHD) given the possibility of creating universal learning environments using technology or conventional tools such as whiteboards or didactic toys, as well as adjusting the learning conditions to the students’ needs. This research work shows the results of using the UDL methodology in physics in two different educational contexts.